Influência da ansiedade na qualidade do sono de pessoas idosas da comunidade - Oliveira, Julia Fernandez (Universidade Federal de São Carlos, 2024)
Objectives: To investigate the association between anxiety and sleep quality in elderly people cared for in Family Health Units. Methods: This is a descriptive and cross-sectional study, using a quantitative approach. Participants were divided into groups with and without anxiety for comparative analyzes of sleep quality. Data collection was carried out using a characterization form with specific questions about anxiety and the Pittsburgh Sleep Quality Index. Descriptive and comparative statistical analyzes were performed. All guidelines of Resolution no. 466/12 of the National Health Council for research involving human beings. Results: The sample was predominantly female (54.4%), married (93.6%), black or mixed race (48.0%), Catholic (55.2%) and retired (80.0%) with perception of insufficient income (57.6%). The average age was 69.94 years and 3.03 years of education. Individual and family income were R$1,198.51 and R$2,319.97, respectively. The prevalence of anxiety was 34.4%. Regarding sleep quality, 24.8% had good quality, 52% had poor sleep quality and 23.2% had sleep disorders. Conclusion: The group with anxiety had a higher average total score of (poor) sleep quality – 9.40 points (Md=9.00; SD=4.40) when compared to the group without anxiety – 6.48 points ( Md=6.00; SD=3.30). This difference between groups was significant. Therefore, it can be concluded that there is a higher proportion of individuals with sleep disorders in the anxiety group.
Influence of anxiety on the quality of sleep of community-dwelling older people
Keywords: Ansiedade; Sono; Pessoa idosa; CIENCIAS DA SAUDE